Food Security Assessment Framework in Armenia: Key Aspects for Further Development - Karine Harutyunyan; Lilit Hakobyan (International Journal of Agricultural Sciences, 2021)
Comprehensive assessment of the Food security situation, analyses of its trends, and early projections are not simple tasks and, therefore, require the application of a well-developed methodological framework and tools. The present article is dedicated to the Food security assessment framework in Armenia, identification of shortfalls in its methodology, and drawing practical recommendations for improvement. In general, Food security assessment in Armenia is based on methodological guidelines provided by UN FAO. However, there is room to improve adaptation in some areas, address local specifics and needs, and enlarge applied tools. Particularly, we discuss the following potential directions for further improvements: 1) synchronization of existing statistical systems and introduction of mutual verification and adjustment mechanisms, 2) adjustments in the calculation of food consumption volumes and food self-sufficiency data, 3) introduction of new aggregated and integral indicators for reflecting different aspects of the Food security situation and 4) improve timelines for data availability, especially period of summarizing and publication of Living Conditions Survey results. It should be noted that, although the discussion is based on the methodology of Food security assessment in Armenia, the issues raised relate to many developing countries around the world, which mostly use the same methodological framework.